Al-Uddah Fi Sharhil Umdah - Imam Muwafaq al-Din Abu Muhammad ibn Qudamah al-Maqdassiy (Dar ibn Rajab & Dar al-Fawa'id)
This Book is Concerning the Jurisprudence (Fiqh) of Imam of the Sunna, Ahmad ibn Hanbal ash-Shaibani (may Allah be well pleased with him) by Shaikh al-Islam Imam al-Muwaffaq ibn Qudama (A.H. 541-620) was one of the luminaries of his day and age.